ANALISIS PENGARUH SISTEM JUST IN TIME DALAM MENUNJANG KELANCARAN PROSES PRODUKSI : STUDI KASUS PADA PT. SIIX ELECTRONICS INDONESIA - Jaya, Hendry (Universitas Riau Kepulauan, 2014)
Every company in their production activities will require supplies of raw materials. With supplies of raw materials, the company is expected to carry out the production process according to the needs or demands of consumers. Just in time systems are implemented in the PT. Siix Electronics Indonesia has not run optimally. It can be seen from production activities that can’t reach the target because there are a lot of raw material supply defective and insufficient supply of raw materials. Forming members to check in source place of raw material suppliers (source inspection) with the aim to help smooth the process of production and to optimize the the just-in-time system.To perform this essay, the author conducted research at PT. SIIX Electronics Indonesia is located in Batamindo Industrial Park, Batam. Data obtained from this study obtained from direct observation and interviews with employees who are competent in this field.Based on these studies, the authors can find out about the influence of just-in-time systems in the procurement of raw materials to support the production process.Keywords: Supplier, Production Performance, Source inspection